By-Products of Olive Oil in the Service of the Deficiency of Food Antioxidants: The Case of Butter - Hind Mikdame; Ezzahra Kharmach; Nour Elhouda Mtarfi; Karima Alaoui; Mohamed Ben Abbou; YAhya Rokni; Zineb Majbar; Mustapha Taleb; Zakia Rais (Journal of Food Quality)
Further downstream in the olive oil extraction process, the Mediterranean Basin faces a serious environmental threat caused by olive waste. Despite their polluting profile, olive waste is considered to be a very rich source of natural antioxidants, such as polyphenols. In this study, the latter was valued as a source of natural antioxidants and compared with a synthetic antioxidant ascorbic acid. Concentrations of 2, 4, 6, and 8 mg of the olive mill waste water as well as pomace and ascorbic acid are added to butter (commercial butter) and placed under storage conditions in the oven (accelerated test: 60°C) for 3 months. The alteration of the butter used was followed by determination of the peroxide value and acidity and microbiological analysis. The results obtained show that butters containing olive by-products have undergone less marked oxidative deterioration than those of the control (without additives). The best oxidative stability of butter was achieved by adding 80 mg/kg of butter, a result comparable with that obtained by adding ascorbic acid.